Impacts of the Fukushima Nuclear Accident on Fish and Fishing Grounds 2015
DOI: 10.1007/978-4-431-55537-7_18
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium Concentrations in the Muscle and Eggs of Salmonids from Lake Chuzenji, Japan, After the Fukushima Fallout

Abstract: Approximately 18 months (September-December 2012) after the Fukushima Dai-ichi Nuclear Power Plant accident, elevated radiocesium concentrations were detected in muscle and egg samples from masu salmon ( Oncorhynchus masou ), kokanee ( Oncorhynchus nerka ), brown trout ( Salmo trutta ), and lake trout ( Salvelinus namaycush ) from the Lake Chuzenji system, central Honshu Island, Japan (160 km from the station). Mean muscle concentrations were 142.9-249.2 Bq/ kg-wet, and mean egg concentrations were 38.7-79.0 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A similar relationship was observed in the present study, where the quantity of radiocesium deposited in lakeside soil decreased with distance from the FNPP. However, this relationship has not been found in all of northeastern Japan because the pollution did not spread concentrically from Lake Tagokura 12 ± 10 3 9.0 ± 3.7 4 the FNPP; For example, Lake Chuzenji (located southwest of the FNPP) and Lake Tagokura are both located roughly 160 km from the FNPP in linear distance, but radiocesium concentrations in the muscle of salmonids in 2012 were 142.9-249.2 Bq/kg wet mass in Lake Chuzenji [10] and only 12 Bq/kg wet mass in Lake Tagokura (Table 5, whitespotted char in sixth row). In addition, there is some evidence that different levels of radiocesium contamination in fish among lakes can also be caused by variation in retention time [19], depth [20], lake water hardness and conductivity [21,22], suspended sediment concentration, and temperature [7].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A similar relationship was observed in the present study, where the quantity of radiocesium deposited in lakeside soil decreased with distance from the FNPP. However, this relationship has not been found in all of northeastern Japan because the pollution did not spread concentrically from Lake Tagokura 12 ± 10 3 9.0 ± 3.7 4 the FNPP; For example, Lake Chuzenji (located southwest of the FNPP) and Lake Tagokura are both located roughly 160 km from the FNPP in linear distance, but radiocesium concentrations in the muscle of salmonids in 2012 were 142.9-249.2 Bq/kg wet mass in Lake Chuzenji [10] and only 12 Bq/kg wet mass in Lake Tagokura (Table 5, whitespotted char in sixth row). In addition, there is some evidence that different levels of radiocesium contamination in fish among lakes can also be caused by variation in retention time [19], depth [20], lake water hardness and conductivity [21,22], suspended sediment concentration, and temperature [7].…”
Section: Discussionmentioning
confidence: 94%
“…Within individual lakes, the Japanese government has restricted the fisheries of those species whose radioactivity exceeds the Japanese standard contamination limit for foods (100 Bq/ kg wet mass for 134 Cs + 137 Cs). However, levels of radiocesium contamination among individuals within conspecifics have also been found to differ among habitats [8][9][10], and the causes of these differences are uncertain. Lake fish are an important food source and are also the target of recreational fishing in Japan.…”
Section: Introductionmentioning
confidence: 97%
“…Signifi cant differences between piscivorous fi sh and others were examined by a t test. Different small letters after number entries indicates signifi cant difference ( P < 0.05) (Cited from Matsuda et al 2015 ) muscle of salmonids in 2012 were 142.9-249.2 Bq kg −1 wet mass in Lake Chuzenji and only 12 Bq kg −1 wet mass in Lake Tagokura (Yamamoto et al 2014a ). In addition, there is some evidence that different levels of radiocesium contamination of fi sh among lakes can also be caused by variation in retention time (Fukushima and Arai 2014 ), depth (Broberg et al 1995 ), lake water hardness and conductivity (Hakanson et al 1992 ;Särkkä et al 1995 ), suspended sediment concentration, and temperature (Rowan and Rasmussen 1994 ).…”
Section: Geographic Differences In Levels Of Radiocesium Contaminationmentioning
confidence: 99%
“…For example, in the Agano River basin in Fukushima,137 Cs contamination of carnivorous salmonids was roughly twice that of the herbivore ayu Plecoglossus altivelis (Mizuno and Kubo 2013 ). However, levels of radiocesium contamination among individuals within conspecifi cs have also been found to differ among habitats (Iguchi et al 2013 ;Mizuno and Kubo 2013 ;Yamamoto et al 2014a ), and the causes of these differences are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Ayabe et al (2014) reported that radiocesium concentrations in a forest floor-inhabiting web spider (Nephila clavata) increased according to radiation dose rate, which depended on distance from the FNPP at 1.5 years after the FNPP accident. Previous studies of aquatic habitats have mostly surveyed freshwater fish species (e.g., Iguchi et al, 2013;Fukushima and Arai, 2014;Yamamoto et al, 2014), although several other taxa have been examined (aquatic insects, Yoshimura and Akama, 2014; anuran tadpoles, Sakai et al, 2014). To clarify the overall flow and distribution of radiocesium in a forest ecosystem, animals that connect the terrestrial and aquatic food webs must be carefully monitored (Murakami et al, 2014).…”
Section: Introductionmentioning
confidence: 99%